PENERAPAN MODEL PEMBELAJARAN PBL UNTUK MENINGKATKAN HASIL BELAJAR SISWA TPBO SMKN 2 DEPOK - Islami Fatwa; Esta Larosa; Munzir Absa (Steam Engineering, 2023)
This research aims to determine whether the problem-based learning model can improve student learning outcomes in the subject of automotive engineering basic work in class X Automotive Body Repair Techniques (TPBO) SMK N 2 Depok, Sleman Yogyakarta. This type of research is Classroom Action Research through 2 cycles where there are four stages carried out, namely (1) planning, (2) implementation, (3) observation, and (4) reflection which leads to an increase in student learning outcomes. The subjects in this Classroom Action Research were class X TPBO SMK N 2 Depok even semester students. Based on data analysis and results of Classroom Action Research (CAR), it can be concluded that based on the results of student learning tests in cycle I, 8 students (25%) completed their studies, in cycle II, 29 students (90.62%) completed learning by obtaining a value of ≥ 75. Based on the results of observations of student learning activities in the first cycle, 18 students (56.25%) were in the less active category and decreased in the second cycle to 4 students (12.5%). Thus the results of the study indicate that the problem-based learning model can increase student activity and learning outcomes in the basic competence of maintaining measuring instruments in the subject of automotive engineering basic work in class X TPBO students at SMK Negeri 2 Depok, Sleman Regency, Yogyakarta.